Electrophysiological Properties of Substantia Gelatinosa Neurons in the Preparation of a Slice of Middle-Aged Rat Spinal Cord - Li, Yang; Su, Shanchu; Yu, Jiaqi; Peng, Minjing; Wan, Shengjun; Ke, Changbin (Frontiers in Aging Neuroscience, 2021)
Patch-clamp recording in slices generated from the brain or spinal cord has facilitated the exploration of neuronal circuits and the molecular mechanisms underlying neurological disorders. However, the rodents used to generate spinal cord slices in previous studies involving patch-clamp recording have been limited to those in the juvenile or adolescent stage. Here, we applied an N-methyl-D-glucamine HCl (NMDG-HCl) solution that enabled patch-clamp recordings to be performed on the superficial dorsal horn neurons in slices derived from middle-aged rats. The success rate of stable recordings from substantia gelatinosa neurons was 34.6% (90/260). When stimulated with a long current, 43.3% of neurons (39/90) presented a tonic firing pattern, which was considered to represent γ-aminobutyric acid (GABA) ergic signals. Presumptive glutamatergic neurons presented 38.9% (35/90) delayed and 8.3% (7/90) single-spike patterns. The intrinsic membrane properties of both neuron types were similar, but delayed (glutamatergic) neurons appeared to be more excitable, as indicated by the decreased latency and rheobase values of the action potential compared with those of tonic (GABAergic) neurons. Furthermore, the glutamatergic neurons integrated more excitatory synaptic transmission. We demonstrated that the NMDG-HCl cutting solution could be used to prepare middle-aged rodent spinal cord slices for patch-clamp recording. Combined with other techniques, this preparation method might permit the further study of how the spinal cord functions in the pathological processes that occur during aging-associated diseases.